Chemical modification of starch from fruit seeds: Methods, properties, and applications - Ventura Avalos, Yulissa Maribel (2024)
The fruit seeds, commonly regarded as waste after consuming the fresh pulp, emerge as a source of unconventional starch with innovative potential. This study focuses on highlighting the significance of these seeds by exploring chemical modification methods in this starch source that add value by transforming their properties. The review emphasizes the influence of key factors such as the type of chemical reagent, its concentration, reaction parameters (pH, temperature, time), and the botanical source of the seed on the degree of modification and the resulting morphological and functional properties of the starch. The importance of specific conditioning during the chemical modification process is underscored, as it significantly contributes to enhancing the properties of the modified starch derived from fruit seed. In this regard, new perspectives are opened to efficiently harness fruit seeds, turning them into a valuable source of starch with diverse applications in both the food and non-food industries.